Starch-based hard carbon and preparation method thereof, negative electrode plate, sodium ion battery and power-related equipment
Through esterification, oxidative crosslinking and carbonization treatment of starch, phosphorus-nitrogen doped starch-based hardcarbon was prepared, which solved the problems of low capacity and unstable morphology of starch-based hardcarbon, and significantly improved the electrochemical performance of sodium ion batteries.
Patent Information
- Application Number
- CN202411883263.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing starch-based hard carbon has low capacity and is difficult to obtain spherical morphology, which affects the performance of sodium ion batteries.
By esterifying the starch with organic acid, esterified starch is obtained, then oxidative crosslinking is performed, and then mixed with a phosphorus source and nitrogen source ball mill, and finally carbonized under a protective atmosphere to prepare phosphorus-nitrogen doped starch-based hard carbon.
The structure and strength of starch-based hard carbon is improved, the spherical morphology is maintained, and the electrochemical performance is optimized, so that the first discharge specific capacity of sodium ion batteries reaches more than 405mAh/g, the first efficiency is more than 90%, and the cycle stability is significantly improved.
Smart Images

Figure CN119683605A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a starch-based hard carbon and a preparation method thereof, a negative electrode sheet, a sodium ion battery and electrical equipment. Background Art
[0002] Sodium-ion batteries have become an important supplement to lithium-ion batteries in the field of low-speed electric vehicles and energy storage due to their low-cost advantages and excellent high- and low-temperature performance and storage performance. Among the negative electrode materials of sodium-ion batteries, hard carbon not only exhibits excellent cycling ability, but also shows better charging capacity and fast charging performance at low temperatures. Hard carbon is known as a non-graphitizable carbon material, which is characterized by a large number of curved graphite sheets randomly distributed and cannot be reshaped into graphite at temperatures of 3000°C or even higher. The non-graphitizable nature of hard carbon can be attributed to the formation of cross-linked or covalent COC bonds in the precursor. The precursor of hard carbon forms a cross-linked structure and generates defects, micropores and oxygen-containing functional groups during pyrolysis, which greatly inhibits the growth of graphite sheets. Even at high processing temperatures, hard carbon only forms short-range orientation characteristics. In addition, the morphology of hard carbon is porous, linear and microspherical, and usually the hard carbon structure is derived from the precursor.
[0003] Hard carbon products obtained from different precursors have significant performance differences, and the cost structure is also significantly different due to different raw material sources. Currently, biomass-based hard carbon has become the mainstream of hard carbon industrialization due to its moderate process and cost.
[0004] However, the consistency and ash content of biomass raw materials have greatly increased the uncertainty of hard carbon materials. The structure of biomass raw materials is affected by many factors such as season, origin, growth status, environment, etc., and the consistency of biomass-based hard carbon performance cannot be guaranteed.
[0005] In addition, the purification and pickling processes also greatly increase the process cost and environmental pollution of biomass-based hard carbon, causing biomass-based hard carbon to lose its natural low-cost advantage. The ash content and composition will also affect the consistency of battery cell performance.
[0006] Starch is a natural high molecular carbohydrate, which can improve the carbon yield due to its low ash content and ability to maintain the natural spherical morphology of starch. The spherical morphology has great practical value in electrochemical energy storage, including high packing density, low surface area to volume ratio and maximum structural stability.
[0007] However, when starch-based hard carbon is used as the negative electrode material of sodium-ion batteries, it will seriously affect the battery capacity due to its low initial coulombic efficiency (ICE) and poor conductivity. In addition, starch-based hard carbon will form a molten state during the preparation process, which is not conducive to the structural regulation of the material during the carbonization process and the formation of a spherical morphology, and has also become a major obstacle to the industrialization of starch-based hard carbon. Summary of the invention
[0008] The purpose of the present application is to provide a starch-based hard carbon and a preparation method thereof, a negative electrode sheet, a sodium ion battery and electrical equipment, aiming to solve the problem that the existing starch-based hard carbon has low capacity and is difficult to obtain a spherical morphology.
[0009] To achieve the above objectives, the present application provides a method for preparing starch-based hard carbon, comprising:
[0010] Esterifying starch with organic acid to obtain esterified starch;
[0011] The esterified starch is oxidatively cross-linked to obtain cross-linked starch;
[0012] ball-milling the cross-linked starch with a phosphorus source and a nitrogen source to obtain a precursor;
[0013] The precursor is carbonized under a protective atmosphere to obtain phosphorus-nitrogen doped starch-based hard carbon.
[0014] In some embodiments, at least one of the following conditions is met:
[0015] A. The mass ratio of the starch to the organic acid is (5-10):(1-2);
[0016] B. the organic acid comprises any one of citric acid, maleic anhydride, acetic acid and tartaric acid;
[0017] C. the starch includes any one of corn starch, potato starch, sweet potato starch and pea starch;
[0018] D. the temperature of the esterification reaction is 60 to 120° C.;
[0019] E. The heating rate of the esterification reaction is 1 to 5°C / min;
[0020] F. The esterification reaction time is 3-6h.
[0021] In some embodiments, after the esterification reaction, the step further includes: washing the esterified starch after the reaction with acetone, and drying it in a vacuum drying oven at a temperature of 50 to 90°C.
[0022] In some embodiments, at least one of the following conditions is met:
[0023] A. the oxidative crosslinking is carried out in a muffle furnace;
[0024] B. The temperature of the oxidative crosslinking is 200-400°C;
[0025] C. The heating rate of the oxidative crosslinking is 1 to 2°C / min;
[0026] D. The reaction time of the oxidative crosslinking is 2 to 15 hours;
[0027] E. The oxygen flow rate during the oxidative cross-linking is 100-250 mL / min.
[0028] In some embodiments, at least one of the following conditions is met:
[0029] A. The mass ratio of the cross-linked starch to the phosphorus source and the nitrogen source is (1-10):1;
[0030] Optionally, the mass ratio of the cross-linked starch to the phosphorus source and the nitrogen source is (5-10):1;
[0031] B. The rotation speed of the ball mill is 300-500 rpm;
[0032] C. The ball milling time is 2 to 6 hours;
[0033] D. The phosphorus source and nitrogen source include at least one of diammonium phosphate, diammonium hydrogen phosphate, and ammonium polyphosphate.
[0034] In some embodiments, the carbonization includes pre-carbonization and high-temperature carbonization, and satisfies at least one of the following conditions:
[0035] A. The pre-carbonization temperature is 500-800°C;
[0036] B. The temperature of the high temperature carbonization is 1200-1700°C;
[0037] C. The holding time of the pre-carbonization and the high temperature carbonization is independently 2 to 5 hours;
[0038] D. The heating rates of the pre-carbonization and the high-temperature carbonization are independently 2-5°C / min.
[0039] The present application also provides a starch-based hard carbon, which is prepared by the above-mentioned method for preparing starch-based hard carbon.
[0040] The present application also provides a negative electrode sheet, comprising the above-mentioned starch-based hard carbon.
[0041] The present application also provides a sodium ion battery, comprising the above-mentioned negative electrode sheet.
[0042] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.
[0043] Compared with the prior art, the beneficial effects of this application include:
[0044] The preparation method of starch-based hard carbon provided in the present application first consumes hydroxyl groups and hydrogen atoms in starch through organic acid esterification to ensure that a molten state will not be formed during the subsequent oxidative crosslinking and carbonization process, so as to improve the structure and strength of the carbon skeleton, and it is easier to introduce functional groups and doping atoms; in the oxidative crosslinking process, the oxidative crosslinking mainly plays the role of introducing oxygen-containing functional groups mainly based on carbonyl groups, and strengthens the degree of crosslinking, so that subsequent carbonization can better dope phosphorus and nitrogen atoms, and form a better spherical structure, and further improve the subsequent carbonization yield. And mixed carbonization with phosphorus and nitrogen sources can directly complete the pore-making process and phosphorus-nitrogen atom doping process during the heating process, and the open pores can be converted into closed pores during the high temperature constant temperature process, so that the prepared starch-based hard carbon material has excellent structure and surface groups and heteroatoms, thereby optimizing the kinetic properties of starch-based hard carbon materials.
[0045] The starch-based hard carbon provided in the present application has low ash content and can maintain the natural spherical morphology of starch, thereby further improving the consistency and cycle stability of the battery cell.
[0046] The sodium ion battery provided in the present application can achieve a first discharge specific capacity of more than 405 mAh / g, a first efficiency of more than 90%, and a capacity retention rate of more than 90% after 500 cycles of charge and discharge at room temperature of the finished battery, with excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0048] Figure 1 This is a schematic diagram of the process for preparing starch-based hard carbon of the present application;
[0049] Figure 2 is a SEM image of phosphorus-nitrogen doped starch-based hard carbon particles of Example 1;
[0050] Figure 3 is the XRD pattern of phosphorus-nitrogen doped starch-based hard carbon particles of Example 1;
[0051] Figure 4 This is a graph showing the charge and discharge test results of the sodium ion battery of Example 1. DETAILED DESCRIPTION
[0052] As used herein:
[0053] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0054] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0055] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0056] In these examples, parts and percentages are by mass unless otherwise indicated.
[0057] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0058] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0059] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0060] This application provides a method for preparing starch-based hard carbon. Figure 1 ,include:
[0061] S100: esterifying starch with an organic acid to obtain esterified starch;
[0062] S200: oxidatively cross-linking the esterified starch to obtain cross-linked starch;
[0063] S300: ball-milling the cross-linked starch with a phosphorus source and a nitrogen source to obtain a precursor;
[0064] S400: carbonizing the precursor under a protective atmosphere to obtain phosphorus-nitrogen doped starch-based hard carbon.
[0065] The preparation method of starch-based hard carbon provided in the present application first consumes hydroxyl groups and hydrogen atoms in starch through organic acid esterification to ensure that a molten state will not be formed during the subsequent oxidative crosslinking and carbonization process, so as to improve the structure and strength of the carbon skeleton, and it is easier to introduce functional groups and doping atoms; in the oxidative crosslinking process, the oxidative crosslinking mainly plays the role of introducing oxygen-containing functional groups mainly based on carbonyl groups, and strengthens the degree of crosslinking, so that subsequent carbonization can better dope phosphorus and nitrogen atoms, and form a better spherical structure, and further improve the subsequent carbonization yield. And mixed carbonization with phosphorus and nitrogen sources can directly complete the pore-making process and phosphorus-nitrogen atom doping process during the heating process, and the open pores can be converted into closed pores during the high temperature constant temperature process, so that the prepared starch-based hard carbon material has excellent structure and surface groups and heteroatoms, thereby optimizing the kinetic properties of starch-based hard carbon materials.
[0066] In some embodiments, the mass ratio of starch to organic acid in step S100 is (5-10):(1-2), for example, it can be 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 5:2, 6:2, 7:2, 8:2, 9:2, 10:2 or any ratio between (5-10):(1-2).
[0067] In some embodiments, the organic acid in step S100 includes any one of citric acid, maleic anhydride, acetic acid, and tartaric acid.
[0068] In some embodiments, the starch in step S100 includes any one of corn starch, potato starch, sweet potato starch, and pea starch.
[0069] In some embodiments, the temperature of the esterification reaction in step S100 is 60-120°C, for example, it can be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C or any value between 60 and 120°C; the heating rate of the esterification reaction is 1 to 5°C / min; and the time of the esterification reaction is 3-6h.
[0070] In some embodiments, after the esterification reaction of step S100, the further step includes: rinsing the esterified starch after the reaction with acetone, and drying it in a vacuum drying oven, and the drying temperature is 50-90°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or any value between 50 and 90°C.
[0071] In some embodiments, the oxidative crosslinking of step S200 is performed in a muffle furnace; the temperature of the oxidative crosslinking is 200-400°C, for example, it can be 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C or any value between 200 and 400°C; the heating rate of the oxidative crosslinking is 1-2°C / min; the reaction time of the oxidative crosslinking is 2-15h, for example, it can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h The oxygen flow rate for oxidative cross-linking is 100-250 mL / min, for example, it can be 100 mL / min, 110 mL / min, 120 mL / min, 130 mL / min, 140 mL / min, 150 mL / min, 160 mL / min, 170 mL / min, 180 mL / min, 190 mL / min, 200 mL / min, 210 mL / min, 220 mL / min, 230 mL / min, 240 mL / min, 250 mL / min or any value between 100 and 250 mL / min.
[0072] In some embodiments, the mass ratio of the cross-linked starch to the phosphorus source and the nitrogen source in step S300 is (1-10): 1, for example, it can be 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1 or any ratio between (1-10): 1. Optionally, the mass ratio of the cross-linked starch to the phosphorus source and the nitrogen source is (5-10): 1.
[0073] In some embodiments, the phosphorus source and nitrogen source in step S300 include at least one of diammonium phosphate, diammonium hydrogen phosphate, and ammonium polyphosphate.
[0074] In some embodiments, the rotation speed of the ball mill in step S300 is 300-500 rpm, for example, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm or any value between 300 and 500 rpm; the ball milling time is 2 to 6 hours.
[0075] In some embodiments, the carbonization in step S400 includes pre-carbonization and high-temperature carbonization, and the temperature of the pre-carbonization is 500-800°C, for example, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, ℃, 730℃, 740℃, 750℃, 760℃, 770℃, 780℃, 790℃, 800℃ or any value between 500 and 800℃; the temperature of high temperature carbonization is 1200-1700℃, for example, it can be 1200℃, 1250℃, 1300℃, 1350℃, 1400℃, 1450℃, 1500℃, 1550℃, 1600℃, 1650℃, 1700℃ or any value between 1200 and 1700℃.
[0076] In some embodiments, the holding time of the pre-carbonization and the high-temperature carbonization is independently 2 to 5 hours; the heating rates of the pre-carbonization and the high-temperature carbonization are independently 2 to 5° C. / min.
[0077] The present application also provides a starch-based hard carbon, which is prepared by the above-mentioned method for preparing starch-based hard carbon.
[0078] The starch-based hard carbon provided in the present application has low ash content and can maintain the natural spherical morphology of starch, thereby further improving the consistency and cycle stability of the battery cell. It has high sphericity and low porosity.
[0079] The present application also provides a negative electrode sheet, comprising the above-mentioned starch-based hard carbon, which has a high compaction density and a high surface density.
[0080] The present application also provides a sodium ion battery, including the above-mentioned negative electrode sheet, which has high initial efficiency, high capacity, and excellent cycle performance.
[0081] The sodium ion battery provided in the present application can achieve a first discharge specific capacity of more than 405 mAh / g, a first efficiency of more than 90%, and a capacity retention rate of more than 90% after 500 cycles of charge and discharge at room temperature of the finished battery, with excellent electrochemical performance.
[0082] The present application also provides an electrical device, including the above-mentioned sodium ion battery, which has high energy density and long cycle life.
[0083] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0084] Example 1
[0085] This embodiment provides a starch-based hard carbon, and the preparation method thereof comprises the following steps:
[0086] Starch and maleic anhydride were mixed evenly in a mortar at a mass ratio of 1:5, and placed in a homogenizer, and heated at 80°C for esterification reaction for 3 hours at a heating rate of 5°C / min; the esterified starch after the reaction was rinsed with acetone and dried in a vacuum drying oven at a drying temperature of 50°C to obtain esterified starch.
[0087] The dried esterified starch was oxidatively cross-linked in a muffle furnace to obtain cross-linked starch. The reaction temperature was 300°C, the reaction time was 2h, the oxygen flow rate was 250mL / min, and the oxidative cross-linking heating rate was 2°C / min.
[0088] The cross-linked starch and diammonium phosphate were mixed by ball milling at a mass ratio of 5:1, with a ball milling speed of 500 rpm and a ball milling time of 2 hours to obtain a precursor.
[0089] Place the precursor into a high-temperature carbonization furnace, introduce a protective gas (argon atmosphere) for pre-carbonization and high-temperature carbonization. Heating rate is 5°C / min to 700°C, keeping temperature for 2 hours, then heating rate is 2°C / min to 1300°C, keeping temperature for 3 hours. Cool naturally; take out the material, crush and sieve it to a mesh size of 300 to obtain the phosphorus-nitrogen doped starch-based hard carbon particles of Example 1. The SEM image of the phosphorus-nitrogen doped starch-based hard carbon particles obtained in Example 1 is shown as follows. Figure 2 The XRD results are shown in Figure 3 shown.
[0090] This embodiment also provides a negative electrode sheet, and the preparation method thereof comprises the following steps:
[0091] The phosphorus-nitrogen doped starch-based hard carbon particles obtained in Example 1, the conductive agent (SP) and the binder (CMC, SBR) were mixed evenly with a certain amount of deionized water in a mass ratio of 94:2:2:2 and then coated on the current collector to prepare a negative electrode sheet for a sodium ion battery.
[0092] Example 2
[0093] This embodiment provides a starch-based hard carbon, and the preparation method thereof comprises the following steps:
[0094] Starch and tartaric acid were mixed evenly in a mortar at a mass ratio of 1:5, and placed in a homogenizer, and heated at 80°C for esterification reaction for 3 hours at a heating rate of 5°C / min; the esterified starch after the reaction was rinsed with acetone and dried in a vacuum drying oven at a drying temperature of 50°C to obtain esterified starch.
[0095] The dried esterified starch was oxidatively cross-linked in a muffle furnace to obtain a cross-linked starch. The reaction temperature was 300°C, the reaction time was 2h, the oxygen flow rate was 250mL / min, and the oxidative cross-linking heating rate was 2°C / min.
[0096] The cross-linked starch and diammonium phosphate were mixed by ball milling at a mass ratio of 5:1, with a ball milling speed of 500 rpm and a ball milling time of 2 hours to obtain a precursor.
[0097] The precursor was placed in a high-temperature carbonization furnace, and a protective gas (argon atmosphere) was introduced for pre-carbonization and high-temperature carbonization. The temperature was raised to 700°C at a heating rate of 5°C / min, and the holding time was 2h, and then the temperature was raised to 1300°C at a heating rate of 2°C / min, and the holding time was 3h. Natural cooling was performed; the material was taken out, crushed and sieved, and the mesh size was 300 meshes, and the phosphorus-nitrogen doped starch-based hard carbon particles of Example 2 were obtained.
[0098] This embodiment also provides a negative electrode sheet, and the preparation method thereof comprises the following steps:
[0099] The phosphorus-nitrogen doped starch-based hard carbon particles obtained in Example 2, the conductive agent (SP) and the binder (CMC, SBR) were mixed evenly with a certain amount of deionized water in a mass ratio of 94:2:2:2 and then coated on the current collector to prepare a negative electrode sheet for a sodium ion battery.
[0100] Example 3
[0101] This embodiment provides a starch-based hard carbon, and the preparation method thereof comprises the following steps:
[0102] Starch and maleic anhydride were mixed evenly in a mortar at a mass ratio of 1:5, and placed in a homogenizer, and heated at 80°C for esterification reaction for 3 hours at a heating rate of 5°C / min; the esterified starch after the reaction was rinsed with acetone and dried in a vacuum drying oven at a drying temperature of 50°C to obtain esterified starch.
[0103] The dried esterified starch was oxidatively cross-linked in a muffle furnace to obtain cross-linked starch. The reaction temperature was 300°C, the reaction time was 2h, the oxygen flow rate was 250mL / min, and the oxidative cross-linking heating rate was 2°C / min.
[0104] The cross-linked starch and diammonium phosphate were mixed in a mass ratio of 2:1 by ball milling at a ball milling speed of 500 rpm for 2 hours to obtain a precursor.
[0105] The precursor was placed in a high-temperature carbonization furnace, and a protective gas (argon atmosphere) was introduced for pre-carbonization and high-temperature carbonization. The temperature was raised to 700°C at a heating rate of 5°C / min, and the holding time was 2h, and then the temperature was raised to 1300°C at a heating rate of 2°C / min, and the holding time was 3h. Natural cooling was performed; the material was taken out, crushed and sieved, and the mesh size was 300 meshes, and the phosphorus-nitrogen doped starch-based hard carbon particles of Example 3 were obtained.
[0106] This embodiment also provides a negative electrode sheet, and the preparation method thereof comprises the following steps:
[0107] The phosphorus-nitrogen doped starch-based hard carbon particles obtained in Example 3, the conductive agent (SP) and the binder (CMC, SBR) were mixed evenly with a certain amount of deionized water in a mass ratio of 94:2:2:2 and then coated on the current collector to prepare a negative electrode sheet for a sodium ion battery.
[0108] Example 4
[0109] This embodiment provides a starch-based hard carbon, and the preparation method thereof comprises the following steps:
[0110] Starch and citric acid were mixed evenly in a mortar at a mass ratio of 1:5, and placed in a homogenizer, and heated at 80°C for esterification reaction for 3 hours at a heating rate of 5°C / min; the esterified starch after the reaction was rinsed with acetone and dried in a vacuum drying oven at a drying temperature of 50°C to obtain esterified starch.
[0111] The dried esterified starch was oxidatively cross-linked in a muffle furnace to obtain cross-linked starch. The reaction temperature was 300°C, the reaction time was 2h, the oxygen flow rate was 250mL / min, and the oxidative cross-linking heating rate was 2°C / min.
[0112] The cross-linked starch and diammonium phosphate were mixed in a mass ratio of 2:1 by ball milling at a ball milling speed of 500 rpm for 2 hours to obtain a precursor.
[0113] The precursor was placed in a high-temperature carbonization furnace, and a protective gas (argon atmosphere) was introduced for pre-carbonization and high-temperature carbonization. The temperature was raised to 700°C at a heating rate of 5°C / min, and the holding time was 2h, and then the temperature was raised to 1300°C at a heating rate of 2°C / min, and the holding time was 3h. Natural cooling was performed; the material was taken out, crushed and sieved, and the mesh size was 300 meshes, and the phosphorus-nitrogen doped starch-based hard carbon particles of Example 4 were obtained.
[0114] This embodiment also provides a negative electrode sheet, and the preparation method thereof comprises the following steps:
[0115] The phosphorus-nitrogen doped starch-based hard carbon particles obtained in Example 4, the conductive agent (SP) and the binder (CMC, SBR) were mixed evenly with a certain amount of deionized water in a mass ratio of 94:2:2:2 and then coated on the current collector to prepare a negative electrode sheet for a sodium ion battery.
[0116] Comparative Example 1
[0117] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not have an esterification reaction process, and the starch is directly oxidatively cross-linked.
[0118] Comparative Example 2
[0119] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 does not have an oxidative cross-linking process, and the esterified starch is directly mixed with diammonium hydrogen phosphate and then carbonized.
[0120] Comparative Example 3
[0121] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, diammonium phosphate is replaced with urea, and the cross-linked starch in Comparative Example 3 is mixed with urea and then carbonized, that is, only nitrogen element is doped.
[0122] Comparative Example 4
[0123] The difference between Comparative Example 4 and Example 1 is that the cross-linked starch in Comparative Example 4 is not mixed with diammonium phosphate, and the cross-linked starch is directly carbonized.
[0124] Comparative Example 5
[0125] The difference between Comparative Example 5 and Example 1 is that the esterified starch in Comparative Example 5 is subjected to reduction treatment, the oxygen introduced in the oxidative cross-linking step is replaced by hydrogen, and the oxygen atoms in the esterified starch are reduced and then mixed with diammonium phosphate for carbonization treatment.
[0126] Performance Testing
[0127] The electrochemical performance of the sodium ion battery of the present application was tested by a half-cell test method. The preparation method was as follows: using the negative electrode sheet obtained in each embodiment and comparative example as the negative electrode, the sodium sheet as the positive electrode, and copper foil and aluminum foil as the current collectors of the negative electrode and the positive electrode, respectively, a Celgard 2300 type diaphragm as the diaphragm, and 1MNaPF6 in EC:DMC=1:1 electrolyte produced by Nanjing Mojies Technology Co., Ltd. as the electrolyte, and assembling into a button battery in an argon glove drying box (moisture content is controlled below <15ppm).
[0128] The battery made under the above basic conditions was tested by a computer-controlled tester, with a charging current of 0.1C, a discharging current of 0.1C, and a charge and discharge voltage range of 0 to 3.0V. The hard carbon negative electrode active material used in the test battery was prepared in Example 1. The charge and discharge test results of the battery in Example 1 are shown in FIG. Figure 4 shown.
[0129] Using Examples 1-4 and Comparative Examples 1-5 as samples, the batteries assembled from the above samples were subjected to electrochemical performance tests under the following test conditions: current density of 30 mA / g, voltage range of 0 to 3.0 V. The test results are shown in Table 1.
[0130] Table 1 Electrochemical performance results of sodium ion batteries of various embodiments and comparative examples
[0131]
[0132]
[0133] According to Table 1, the phosphorus-nitrogen doped starch-based hard carbons of Examples 1 to 4 prepared by the scheme of the present application can have high capacity, high capacity retention rate and high initial effect, especially when the mass ratio of the cross-linked starch to diammonium phosphate in Examples 1 and 2 is 5:1, the capacity and initial effect of the starch-based hard carbon obtained are significantly higher than those of Examples 3 and 4, where the mass ratio of the cross-linked starch to diammonium phosphate is 2:1. Increasing the amount of diammonium phosphate will lead to a decrease in initial effect and capacity. According to Examples 3 and 4, different acids will affect the esterification effect and structure of starch, which will ultimately lead to differences in its capacity initial effect and cycle retention rate.
[0134] According to Comparative Examples 1 and 2, the esterification reaction process and the oxidative cross-linking process have a great influence on the performance of starch-based hard carbon. The oxidative cross-linking process is beneficial to improving the capacity. This is because oxidative cross-linking can make the material have more oxygen-containing groups and strengthen the degree of cross-linking, so that the subsequent carbonization can better dope phosphorus and nitrogen atoms and form a better spherical structure.
[0135] According to Comparative Examples 3 and 4, compared with Example 1 doped with phosphorus and nitrogen, the capacity and capacity retention rate of Comparative Example 3 doped with only nitrogen are significantly reduced, but it is still better than the solution of Comparative Example 4 where neither phosphorus nor nitrogen is doped.
[0136] According to Comparative Example 5, it can be seen that the reduction treatment of esterified starch cannot achieve the same effect as the oxidation treatment. The capacity, capacity retention rate and first efficiency of the starch-based hard carbon in Comparative Example 5 are much lower than those in Example 1.
[0137] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0138] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing starch-based hard carbon, characterized in that: include: Esterifying starch with organic acid to obtain esterified starch; The esterified starch is oxidatively cross-linked to obtain cross-linked starch; ball-milling the cross-linked starch with a phosphorus source and a nitrogen source to obtain a precursor; The precursor is carbonized under a protective atmosphere to obtain phosphorus-nitrogen doped starch-based hard carbon.
2. The method for preparing starch-based hard carbon according to claim 1, characterized in that: At least one of the following conditions is met: A. The mass ratio of the starch to the organic acid is (5-10):(1-2); B. the organic acid comprises any one of citric acid, maleic anhydride, acetic acid and tartaric acid; C. the starch includes any one of corn starch, potato starch, sweet potato starch and pea starch; D. the temperature of the esterification reaction is 60 to 120° C.; E. The heating rate of the esterification reaction is 1 to 5°C / min; F. The esterification reaction time is 3-6h.
3. The method for preparing starch-based hard carbon according to claim 1 or 2, characterized in that: After the esterification reaction, the method further comprises: washing the esterified starch after the reaction with acetone and drying it in a vacuum drying oven at a temperature of 50 to 90°C.
4. The method for preparing starch-based hard carbon according to claim 1, characterized in that: At least one of the following conditions is met: A. the oxidative crosslinking is carried out in a muffle furnace; B. The temperature of the oxidative crosslinking is 200-400°C; C. The heating rate of the oxidative crosslinking is 1 to 2°C / min; D. The reaction time of the oxidative crosslinking is 2 to 15 hours; E. The oxygen flow rate during the oxidative cross-linking is 100-250 mL / min.
5. The method for preparing starch-based hard carbon according to claim 1, characterized in that: At least one of the following conditions is met: A. The mass ratio of the cross-linked starch to the phosphorus source and the nitrogen source is (1-10):1; Optionally, the mass ratio of the cross-linked starch to the phosphorus source and the nitrogen source is (5-10):1; B. The rotation speed of the ball mill is 300-500 rpm; C. The ball milling time is 2 to 6 hours; D. The phosphorus source and nitrogen source include at least one of diammonium phosphate, diammonium hydrogen phosphate, and ammonium polyphosphate.
6. The method for preparing starch-based hard carbon according to claim 1, characterized in that: The carbonization includes pre-carbonization and high-temperature carbonization, and satisfies at least one of the following conditions: A. The pre-carbonization temperature is 500-800°C; B. The temperature of the high temperature carbonization is 1200-1700°C; C. The holding time of the pre-carbonization and the high temperature carbonization is independently 2 to 5 hours; D. The heating rates of the pre-carbonization and the high-temperature carbonization are independently 2-5°C / min.
7. A starch-based hard carbon, characterized in that The starch-based hard carbon is prepared by the preparation method of any one of claims 1 to 6.
8. A negative electrode sheet, characterized in that: Including the starch-based hard carbon as described in claim 7.
9. A sodium ion battery, characterized in that: Includes the negative electrode sheet as described in claim 8.
10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.
Citation Information
Patent Citations
Ammonium phosphate doped modified asphalt-based hard carbon negative electrode material and preparation method thereof
CN116216693A
Starch-based hard carbon material as well as preparation method and application thereof
CN118306977A
Hard carbon composite material and preparation method and application thereof
CN118315556A
Starch-based doped hard carbon material as well as preparation method and application thereof
CN118908183A
Water-absorbent starch copolymerisates and method for their preparation.
EP0000247A1
Cited By
Hard carbon negative electrode material and preparation method thereof, negative electrode plate and sodium ion battery
CN121134732A
Sodium-ion battery biomass derived hard carbon negative electrode material and preparation method and application thereof based on cross-linking pore-forming
CN121317693A
A sodium-ion battery biomass-derived hard carbon negative electrode material and a preparation method and application thereof based on cross-linking pore-making
CN121317693B
Controllable spherical hard carbon electrode material based on biomass saccharification and preparation method thereof
CN122035827A